Pengaruh E-Service Quality dan E-Trust terhadap Continuance Intention melalui E-Satisfaction sebagai variabel mediasi (Studi pada pengguna aplikasi MyPertamina) - Yousyta Fany Aurita; Monika Tiarawati (Universitas Negeri Surabaya, 2026)
This study aims to analyse the influence of e-service quality and e-trust on continuance intention, mediated by e-satisfaction, among users of the MyPertamina application. The background of this study is the phenomenon of increasing use of digital public service applications that are not yet fully supported by users' intentions for continuity. This study used a quantitative approach and involved 220 active users of the MyPertamina app, selected through purposive sampling. Data processing and analysis were performed using the Structural Equation Modelling Partial Least Squares (SEM-PLS) method in SmartPLS 3.0. The study's results indicate that e-service quality and e-trust influence continuance intention. E-service quality also influences e-satisfaction, whereas e-trust does not. Furthermore, e-satisfaction does not influence continuance intention. These findings indicate that service quality and user trust in the application are more dominant in shaping the intention to continue using the application than mere user satisfaction. Therefore, the MyPertamina application managers are advised to continue improving service quality and building user trust to foster loyalty and sustainable use of the application.